ANALISIS EFEKTIVITAS CRM DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PASIEN RAWAT INAP DI RS AWAL BROS PANAM - Gusriansyah, Gusriansyah; Zulkarnain, Zulkarnain; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2018)
The purpose of this study is to analyze the effectiveness of CRM andservice quality toward inpatient satisfaction and loyalty of Awal Bros PanamHospital. Data collection technique used questionnaires distributed to patientswho had been treated 2 times or more in Awal Bros Panam Hospital. Data wereanalyzed using path analysis technique. Based on the results of data processingcan be concluded that; 1) The loyalty inpatient were spurious loyalty, itâs meanthat consumer influenced subjective norm that is difficult to choose other hospital,situational factor needed handling patient condition as soon as possible. 2) Themore effectives of CRM implemented would be improves patient satisfaction.Application of CRM could be more effective if the RS given small gift for patientsthose gradually recovering his condition. 3) The higher of service quality wouldbe improves patient satisfaction. The quality of service has needs to be improvedon personal attention aspect of medical personnel to reduce the anxiety ofpatients, the majority of women aged â¥ 51 years during the treatment period. 4)The more effectives of CRM that has been implemented can improve patientloyalty. Patient loyalty can increase if hospital management is able to implementCRM more effectively so that patients are proud and believe in the service ofmedical personnel. 5) The higher the quality of service can increase patientloyalty. The medical personnel have shown a professional understanding andattitude, but still lacking in personal attention. 6) The more effective CRM that isimplemented can improve patient satisfaction and loyalty. Patients consideredCRM to be effective enough in fulfilling patient satisfaction in procedural care,but the expectation of the patient would want the hospitals appreciation forpatients whose condition is recovering. 7) The higher quality of service canimprove patient satisfaction and loyalty. The most effective quality of service is aclear transparency of information and risks during the treatment. This means thatpatients feel satisfied because they feel handled by medical personnel who work ina professional manner that helped increase loyalties.